Subtilase Cytotoxin Enhances Escherichia coli Survival in Macrophages by Suppression of Nitric Oxide Production through the Inhibition of NF-κB Activation - Tsutsuki, Hiroyasu (American Society for Microbiology, 2012)
Subtilase cytotoxin (SubAB), which is produced by certain strains of Shiga-toxigenic Escherichia coli (STEC), cleaves an endoplasmic reticulum (ER) chaperone, BiP/Grp78, leading to induction of ER stress and caspase-dependent apoptosis. SubAB alters the innate immune response. SubAB pretreatment of macrophages inhibited lipopolysaccharide (LPS)-induced production of both monocyte chemoattractant protein 1 (MCP-1) and tumor necrosis factor α (TNF-α). We investigated here the mechanism by which SubAB inhibits nitric oxide (NO) production by mouse macrophages. SubAB suppressed LPS-induced NO production through inhibition of inducible NO synthase (iNOS) mRNA and protein expression. Further, SubAB inhibited LPS-induced IκB-α phosphorylation and nuclear localization of the nuclear factor-κB (NF-κB) p65/p50 heterodimer. Reporter gene and chromatin immunoprecipitation (ChIP) assays revealed that SubAB reduced LPS-induced NF-κB p65/p50 heterodimer binding to an NF-κB binding site on the iNOS promoter. In contrast to the native toxin, a catalytically inactivated SubAB mutant slightly enhanced LPS-induced iNOS expression and binding of NF-κB subunits to the iNOS promoter. The SubAB effect on LPS-induced iNOS expression was significantly reduced in macrophages from NF-κB1 (p50)-deficient mice, which lacked a DNA-binding subunit of the p65/p50 heterodimer, suggesting that p50 was involved in SubAB-mediated inhibition of iNOS expression. Treatment of macrophages with an NOS inhibitor or expression of SubAB by E. coli increased E. coli survival in macrophages, suggesting that NO generated by macrophages resulted in efficient killing of the bacteria and SubAB contributed to E. coli survival in macrophages. Thus, we hypothesize that SubAB might represent a novel bacterial strategy to circumvent host defense during STEC infection.